Associations and Correlations : Unearth the Powerful Insights Buried in Your Data - Baker, Lee (Packt Publishing, Limited, 2019)
Through this book, you'll learn why most statistical techniques give incorrect results and what you can do to avoid the most common pitfalls. You'll learn how to make sure you get the correct results the first time, every time.